The interactive effects of turbozyme 160 and diet complexity on starter pig growth performance - Lofing, M.L.; Bergstrom, J.R.; Nessmith, W.B. Jr.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
These results suggest that feeding a complex starter diet improves initial (d 0 to 7 postweaning) growth performance of segregated early-weaned pigs. Feeding either a simple or complex diet with added Turbozyme 160 improves feed efficiency from day 0 to 14 postweaning. However, for the overall experimental period, neither a complex diet nor added Turbozyme 160 had any effect on growth performance.
Keywords: Swine; Starter; Performance; Diet complexity; Enzyme